Does more education mean less fun? A comparison of two animal presentations. Issue 1 (25th February 2016) - Mann‐Lang, J. B.; Ballantyne, R.; Packer, J.
Abstract : Animal presentations have the potential to reach zoo and aquarium visitors with powerful conservation messages that inspire environmentally responsible behaviour. However, there is limited information available on the style of presentation that would be most effective in achieving the greatest impact. This research study was designed to investigate the impact of two differently designed dolphin presentations on conservation‐learning outcomes and overall enjoyment of visitors. The results showed that increasing the educational content of the presentation enhanced visitor learning considerably, without detracting from their enjoyment of the presentation. The research provides evidence for the value of animal presentations in the conservation‐education programmes of zoos and aquariums, and provides suggestions of how to increase the impact of such presentations.